ANALISIS STRUKTUR, FUNGSI, DAN MAKNA ENAM CERPEN DALAM KUMPULAN TEKS CERPEN LAYU SATONDEN KEMBANG - Sri Devi Lestari, Gusti Ayu (Humanis, 2015)
This study examines the literature of modern Balinese which has form narative text of a short story. This study which containts six short storiesin collection of short story text Layu Satonden Kembang, namely: Layu Satonden Kembang, Nyesel Tan Mawiguna, Dayu Sari, Tresna Kapialang, Tresnane Tan Katutugang, andWates Wangsa. The purpose of this study is describe the structure, functions, and meaning which contained in the text collections of six stories in Layu Satonden Kembang. This study was used structural theory by Teeuw, semiotic theory by Saussure, and supporting by reception theory. Method and technique was used in this study devided into three steps such as: (1) collecting data was used method of reading and supporting by translation, (2) the analysing data was used qualitative method and analytic descriptive technique, and (3) conclusions the analysis of informal method by diagram technique and support by inductive-deductive knowledge. The conclusions of this study were found intrinsict structure in six short stories text which namely: plot, setting, actor and character, meaning, and message in story. Therefore this study also describing of functions of in six short stories in collection short story text Layu Satonden Kembang for giving knowledge for societies in order to get experiences and learning goodness for through a good life and avoid unsuccesfully. Therefore that meaning is protect societies life.
Keywords: structure, function, meaning